The fragrant flower garden : growing, arranging & preserving natural scents - Bittner, Stefani, 1969-; Harampolis, Alethea (Ten Speed Press, 2024)
"Make your garden and home look and smell heavenly with this accessible gardening guide that explains how to grow fragrant flowers outdoors and bring natural scents indoors by creating floral arrangements, scented beauty products, and more"--